PENGEMBANGAN MANAJEMEN PELAYANAN KALIBRASI ALAT NAVIGASI PENERBANGAN DENGAN PENDEKATAN METODE IMPORTANCE-PERFORMANCE ANALYSIS (IPA) - Munadi Munadi; Ismiyati Ismiyati; Mudjiastuti Handajani (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2021)
Flight safety is very much determined by the performance of navigation aids, as well as thecorrectness of flight procedure guidelines. The BBKFP Center as the only aviationequipment calibration service agency has a strategic role for aviation safety in asustainable manner. The purpose of this research is to map the performance of BBKFPand the assessment of users of calibration services to provide recommendations, inparticular, the future calibration service development strategy, and the management ofcalibration of aviation navigation equipment in general. The research method uses a casestudy with the Importance-Performance Analysis method approach to measuring the extentof the relationship between the level of user satisfaction and the performance of flightnavigation tool calibration services based on 12 standard service indicators. The resultsfound that the highest level of service was the standard document calibration process of100% and the lowest level of service was timeliness of service by 64%. The factor that stillneeds immediate improvement is the timeliness of service and the Management System andService Procedures. While the factors that must be corrected but not immediately theircharacteristics include Complaint Services; Demand-Supply Balance, Service Rates,Service and Internal Supervision Meeting.